Bank Funding Costs for International Banks - Babihuga, Rita (IMF Working Papers; Working Paper ;, 2014)
This paper investigates the determinants of bank funding costs for a sample of internationally active banks from 2001-12. We find that changes in banks' unsecured funding costs are associated with bank-specific characteristics such as an institution's credit worthiness and the return on its market value, and importantly, on the level and quality of capital. Similarly, market factors such as the level of investor risk appetite, as well as shocks to financial markets-notably the US subprime crisis and the Euro Area sovereign debt crisis-have also been key drivers of the sharp rise in bank funding costs. We also find evidence that large systemically important institutions have enjoyed a funding advantage, and that this advantage has risen since the onset of the two crises. With the exception of Euro Area periphery banks, by end-2012 the rise in funding costs had generally been reversed for most major banks as a result of improvments in bank asset quality as well as steps taken to increase resilience, notably higher capitalization. Our results suggest increased capital buffers may potentially support bank lending to the real economy by reducing bank funding costs.